Editorial - Editor, Journal (University of Dar es Salaam Library Journal, 2017)
This Journal issue contains eight papers on cross-cutting issues such as information for forest management, agriculture, biotechnology, food security, information and communication technology, electronic resources, and knowledge management. Click full text for details.